2015
DOI: 10.1016/j.bjorl.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Is it important to repeat the positioning maneuver after the treatment for benign paroxysmal positional vertigo?

Abstract: The study shows that doing the retest after repositioning maneuver of particles in BPPV is effectual, since it has high specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
0
11
0
1
Order By: Relevance
“…However, there is no consensus on recovery: authors such as Oh and Soto‐Varela consider in their studies that the manoeuvre has been successful when patient‐reported vertiginous symptoms disappear and the DHM becomes negative, without specifying whether it should be negative vertigo, nystagmus or both. Babac considers success for negative DHM also without specifying whether if negative manoeuvre is referred to symptoms or just nystagmus; Oliveira for negative nystagmus regardless of patient‐reported symptoms or positional vertigo on the DHM. Most authors, like Pérez‐Fernández, Pérez and López‐Escámez, consider recovery from an episode when no positional nystagmus or vertigo on the DHM is observed, without taking into account the persistence of symptoms in daily life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no consensus on recovery: authors such as Oh and Soto‐Varela consider in their studies that the manoeuvre has been successful when patient‐reported vertiginous symptoms disappear and the DHM becomes negative, without specifying whether it should be negative vertigo, nystagmus or both. Babac considers success for negative DHM also without specifying whether if negative manoeuvre is referred to symptoms or just nystagmus; Oliveira for negative nystagmus regardless of patient‐reported symptoms or positional vertigo on the DHM. Most authors, like Pérez‐Fernández, Pérez and López‐Escámez, consider recovery from an episode when no positional nystagmus or vertigo on the DHM is observed, without taking into account the persistence of symptoms in daily life.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, there is not a unanimous definition of episode recovery among authors: recovery is usually defined as the disappearance of nystagmus on the control DHM, but disappearance of vertigo during DHM and changes in general status (GS) in daily life activities reported by patients at follow-up are also important results. Often, resolution criteria are usually not specified or there is no consensus between authors among CSP-PBBV literature [21][22][23][24][25][26][27][28] .…”
mentioning
confidence: 99%
“…authors to perform a verifying positional test. 23,24 The opening to the horizontal canal is immediately adjacent to the common crus, which increases the risk of canal switch, if verifying positional test is performed earlier. It is speculated that the aggregate of high-mass otoconia are cleared out of canal mostly with lesser number of maneuvers compared with large number of low-mass otoconia dispersed throughout the canal.…”
Section: Videomentioning
confidence: 99%
“…BPPV was first described by Barany in the literature in 1921. [15] He attributed this lesion with otolithic organs. Dix and Hallpike in 1952 first performed provocative positional testing which was named in their honor.…”
Section: Prevalence and Incidencementioning
confidence: 99%